2001
DOI: 10.1097/00005373-200108000-00003
|View full text |Cite
|
Sign up to set email alerts
|

ARDS after Pulmonary Contusion: Accurate Measurement of Contusion Volume Identifies High-Risk Patients

Abstract: Extent of contusion volumes measured using three-dimensional reconstruction allows identification of patients at high risk of pulmonary dysfunction as characterized by development of ARDS. This method of measurement may provide a useful tool for the further study of PC as well as for the identification of patients at high risk of complications at whom future advances in therapy may be directed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
182
2
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(203 citation statements)
references
References 20 publications
5
182
2
14
Order By: Relevance
“…The mean increase in the PCS of 7.9 units was nearly equivalent to an entire hemilung volume. Miller et al, [10] found that in a series of pulmonary contusion detected by CT thorax scan, a mean of 18% of the pulmonary parenchyma was contused, and that the contusion increased by 11% with a repeat CT scan at 24 hours. Moreover, 82% of patients with a contusion of at least 20% developed acute respiratory distress syndrome (ARDS) versus only 22% of patients with a contusion less than 20%.…”
Section: Resultsmentioning
confidence: 99%
“…The mean increase in the PCS of 7.9 units was nearly equivalent to an entire hemilung volume. Miller et al, [10] found that in a series of pulmonary contusion detected by CT thorax scan, a mean of 18% of the pulmonary parenchyma was contused, and that the contusion increased by 11% with a repeat CT scan at 24 hours. Moreover, 82% of patients with a contusion of at least 20% developed acute respiratory distress syndrome (ARDS) versus only 22% of patients with a contusion less than 20%.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] In patients with multiple trauma, if PC occurs, the mortality rate increases from 27% to 56%. In addition, animal experimental studies revealed that after trauma, there are severe local and systemic inflammatory changes, which potentially trigger septic complications, and the organ failure that first develops in this table is respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…The impact energy of 1.96 J was applied to the chest wall. The impact energy (E; in Joules, J) of the falling weight was calculated from the equation: E = mgh (16), where m is the mass of the falling aluminum weight (0.4 kg), g is gravitational acceleration (9.8 m/s 2 ), and h is the height of the weight (50 cm) above the Lexon platform. All experimental rats were observed until they recovered from the procedure.…”
Section: Methodsmentioning
confidence: 99%